Bioremediation Trends on Mitigation of As(III), Cr(VI) and Organic Dyes From Aqueous Medium using Plant and Microbial Biomass: An Overview - Kumar, Ujjwal; Jha, Ashok K.; Thakur, Raghbendra (International Journal of Bio-resource and Stress Management, 2021)
Arsenic, chromium and organic dyes are the prominent carcinogenic agents, posing a serious health hazard. In current scenario, groundwater as well as surface water mostly contaminated by chemical complexes of As (III), Cr (VI) and organic dyes, these are leading hazardous threat to eco-system. Several mitigation techniques of As (III), Cr (VI) and organic dyes are available but efforts are going on to devise a novel method of removal of these toxicants. This review takes into account all the recent advances in the detoxification of contaminated water exploring removal mechanism by biosorption and bioaccumulation. The possibility of the removal of toxic heavy metals from an aqueous medium by plant and bacterial biomass has been discussed. Now a days, bioaccumulation and biosorption from plants and microbial sources has emerged as simple, effective and eco-friendly techniques for decontamination of these chemical compounds from water resources at very low cost. Many agricultural products and solid wastes have also been found suitable decontaminant of toxic heavy metals and dyes. A wide spectrum of medicinal and aromatic plants as well as aquatic plants available in abundance may also be utilized as potential remover of As (III), Cr (VI) and organic dyes. This article explained mechanism and application on detail aspects of bioremediation technology including conventional techniques with recent development. This review shows the trends and development of mitigation stretagies by bioremediation with latest updates.